2021
DOI: 10.1038/s41598-020-80325-x
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection susceptibility influenced by ACE2 genetic polymorphisms: insights from Tehran Cardio-Metabolic Genetic Study

Abstract: The genetic variations among individuals are one of the notable factors determining disease severity and drug response. Nowadays, COVID-19 pandemic has been adversely affecting many aspects of human life. We used the Tehran Cardio-Metabolic Genetic Study (TCGS) data that is an ongoing genetic study including the whole-genome sequencing of 1200 individuals and chip genotyping of more than 15,000 participants. Here, the effect of ACE2 variations by focusing on the receptor-binding site of SARS-CoV-2 and ACE2 cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 57 publications
0
33
0
Order By: Relevance
“…The recent outbreak of COVID‐19 has been leading to an increased number of infected individuals and subsequent mortality worldwide. Although genomic variants can cause differences in the symptoms and contagion of SARS‐CoV‐2 infection, 1 it is essential to evaluate the various aspects of viral pathogenesis to understand the biological pathways relevant to the COVID‐19 pandemic. Long non‐coding RNAs (lncRNAs), RNA molecules longer than 200 nucleotides, can serve as diagnostic biomarkers or therapeutic targets for many diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The recent outbreak of COVID‐19 has been leading to an increased number of infected individuals and subsequent mortality worldwide. Although genomic variants can cause differences in the symptoms and contagion of SARS‐CoV‐2 infection, 1 it is essential to evaluate the various aspects of viral pathogenesis to understand the biological pathways relevant to the COVID‐19 pandemic. Long non‐coding RNAs (lncRNAs), RNA molecules longer than 200 nucleotides, can serve as diagnostic biomarkers or therapeutic targets for many diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamic demonstrated that I468V and K26R may affect binding characteristics between the S protein of the virus and the human ACE2 receptor [16] . Besides K26R, a specific SNP (S331F) was identified in the Iranian population, which could reduce the receptor affinity for the viral Spike protein [17] . DOCK and FireDock simulations identified 6 ACE2 missense variants (A25T, E37K, E75G, I21T, K26R, T55A) with higher affinity for SARS-CoV-2 Spike protein receptor-binding domain for wild type ACE2, and 11 variants (E23K, E35K, I21V, K26E, K68E, M82I, N51D, N58H, S43R, T27A, Y50F) with a lower affinity [18] .…”
Section: Genetic Polymorphisms Affecting the Angiotensin-converting Enzyme 2 Expression ( Table 1 )mentioning
confidence: 99%
“…The latest research on the role of the RAAS pathway in COVID-19 focuses on genetic variations in ACE2 expression among individuals [ 21 ]. A publication by Lanjanian et al [ 21 ] found that some missense variants of the ACE2 receptor have reduced affinity for the COVID-19 spike protein that gains entry into cells. Further investigation in this area may help target future therapies for COVID-19.…”
Section: Introductionmentioning
confidence: 99%